Neotropical palms: from their conservation to economic potential - Martins, Kauanne Karolline Moreno; Vianna, Suelen Alves; Francisconi, Ana Flávia; Scaketti, Matheus; Konzen, Enéas Ricardo; Zucchi, Maria Imaculada (Frontiers in Plant Science, 2024)
Palms (Arecaceae) are an important group of plants widely distributed throughout the world. The Arecaceae family comprises a great diversity of species, however, many of them are threatened with extinction due to their unbridled exploitation in search of economically important resources. An overview of palms biology will be presented, with emphasis on genetics and genomic resources of several species, as well as their socioeconomic impact worldwide, highlighting the main advances in recent research. Our discussion also covers the demand for urgent measures toward conservation and preservation of palms since they play key roles in maintaining biodiversity and providing essential ecosystem services. Fundamentally, this article is to raise awareness about the importance of palms and to encourage the protection and conservation of these valuable species.